2012
DOI: 10.5923/j.ijme.20120204.05
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Cr<SUB>3</SUB>B<SUB>4</SUB> Cermets Cemented by Different Metallic Binders

Abstract: Cr 3 B 4 cermets cemented by cobalt and iron as a metallic b inder up to 20 wt% were prepared by hot pressing at 1500 and 1800℃ under a pressure of 14 and 41 MPa for 1hr. The binder addition enhanced the densification of Cr 3 B 4 cermets due to the formation of liquid metal and its flow into the pores. It is also found that the temperature and pressure have a pronounced effect on densificat ion. The densification of Cr 3 B 4 is enhanced by the addition of cobalt and iron due to the liquid phase format ion, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
(3 reference statements)
1
1
0
Order By: Relevance
“…Knowing the elastic constants also allows an estimation of the Vickers hardness (H V ) based on the calculated B DFT and G DFT using the parametrized relationship shown in eq 1, where κ is Pugh's ratio (G/B). 16 Using eq 1, the estimated H V,Chen for Cr 3 B 4 is 27 GPa, which is in agreement with the experimentally measured value (H V,exp ≈ 26 GPa), 34 compared to other high hardness transition metal borides like WB 4 (H V,exp ≈ 43 GPa) 49 and OsB 2 (H V,exp ≈ 22 GPa). 52 This supports the fact that Cr 3 B 4 is ultraincompressible, but it is not a superhard transition metal boride.…”
Section: ■ Computational Methodssupporting
confidence: 87%
See 1 more Smart Citation
“…Knowing the elastic constants also allows an estimation of the Vickers hardness (H V ) based on the calculated B DFT and G DFT using the parametrized relationship shown in eq 1, where κ is Pugh's ratio (G/B). 16 Using eq 1, the estimated H V,Chen for Cr 3 B 4 is 27 GPa, which is in agreement with the experimentally measured value (H V,exp ≈ 26 GPa), 34 compared to other high hardness transition metal borides like WB 4 (H V,exp ≈ 43 GPa) 49 and OsB 2 (H V,exp ≈ 22 GPa). 52 This supports the fact that Cr 3 B 4 is ultraincompressible, but it is not a superhard transition metal boride.…”
Section: ■ Computational Methodssupporting
confidence: 87%
“…Cr 3 B 4 is a prime example of earth-abundant 3d transition metal boride with moderate experimentally measured hardness (H V = 26 GPa). 34 In this work, we explored the opportunity of enhancing the mechanical properties of Cr 3 B 4 by computationally investigating the chemical bonding through COHP calculation, which revealed that the compound is too electron rich. Therefore, V substitution is employed to optimize the chemical bonding in Cr 3 B 4 by reducing the VE count.…”
Section: ■ Introductionmentioning
confidence: 99%